Job insecurity in fixed-term employment: Theoretical investigation on job engagement, job insecurity, and job satisfaction in fixed-term employment - Kaivonen, Nea Selina (My University, 2023)
Generally, fixed-term employment contracts have a set starting and finishing day. The employ-ment ends on the ending day agreed on the employment contract without additional notice from either of the parties on the set ending day. Fixed-term employment is a way to employ individuals for temporary need of labor. This form of employment can be generally portrayed as flexible and low risk for the employer. However, occasionally fixed-term employment is found unattractive by employees because of its discontinuous nature. Fixed-term employment in relation to job insecurity and work engagement has been a relatively popular topic in prior research. Existing research shows that the discontinuous nature of fixed-term employment contracts may enhance job insecurity and job disengagement. However, some studies show that fixed-term employment may, in fact, enhance work engagement by cre-ating an incentive for continuation of the employment. This thesis is a theoretical overview of prior research including fixed-term employment in rela-tion to work engagement, job insecurity, and job satisfaction. Prior research is used to highlight important definitions, highlight the main points of prior studies’ findings and to reflect on other research. The aim is to get prior research to converse with one another. This thesis includes an empirical example of a case conducted in an anonymous organization. The example case study consists of ten interviews held with the organization’s employees and their leader. The purpose of the case is not to draw conclusions, but rather to act as an example that supports the existing theories, which are reflected in relation to the case findings.

Määräaikaisissa työsuhteissa on yleisesti ennalta määritetty aloitus- ja päättymispäivä. Työ-suhde päättyy työsopimukseen ennalta sovittuna päätymispäivänä ilman erillistä irtisanomisil-moitusta kummankaan osapuolen aloituksesta. Määräaikainen työsuhde on tapa työllistää ih-misiä määräaikaiselle, työvoimaa vaativalle ajankohdalle. Kyseinen työsuhdemuoto voidaan yleisesti tulkita joustavana ja matalariskisenä työnantajan näkökulmasta. Työntekijät saattavat kuitenkin kaihtaa määräaikaisia työsuhteita niiden jatkumattomuutensa vuoksi. Aiemmissa tutkimuksissa määräaikaisten työsuhteiden suhde työn epävarmuuteen ja työn imuun on suhteellisen suosittu tutkimuskohde. Aiemmat tutkimukset osoittavat, että työsuh-teen jatkumattomuus saattaa kasvattaa työn epävarmuutta sekä laskea työn imua. Toisaalta jot-kut tutkimukset osoittavat, että työn epävarmuus voi itse asiassa kasvattaa työn imua, sillä työn määräaikaisuus luo motivaatiotekijän panostaa työhön, jotta työsuhde jatkuisi myös määräai-kaisuuden jälkeen. Tämä pro gradu -tutkielma on teoreettinen yleiskatsaus aiempiin tutkimuksiin määräaikaisista työsuhteista ja niiden yhteydestä työn imuun, työn epävarmuuteen sekä työtyytyväisyyteen. Aiemmista tutkimuksista nostetaan esille tärkeimmät määritelmät, tutkimusten löydökset sekä vertaillaan niitä keskenään. Pyrkimys on saada aiemmat tutkimukset keskustelemaan keske-nään. Tässä pro gradu -tutkielmassa esitetään myös empiirinen esimerkki case-tutkimuksen muodossa nimeämättömästä organisaatiosta. Kyseinen esimerkkitutkimus pitää sisällään kymmenen haas-tattelua organisaation työntekijöiltä ja heidän johtajaltaan. Case-esimerkin tarkoitus ei ole vetää vahvoja johtopäätöksiä, vaan pääasiassa toimia tukevana esimerkkinä aiemmalle tutkimukselle, joita heijastellaan case-esimerkin löydöksiin.
Keywords: fi=Julkisjohtaminen|en=Public Management|; fi=Hallintotieteiden maisteriohjelma|en=Master's Programme in Administrative Sciences|